PC0003 Prevalence of musculoskeletal diseases and its treatment in the elderly. (23rd January 2014) - Julian, R.; Castell, V.; Gomez, I.; Mateo, C.; Sanchez, M.; Lopez-Gonzalez, P.; Sanchez, P.
Abstract : Background: Aging population means an increase in the prevalence of degenerative diseases like osteoarthritis and other musculoskeletal conditions and therefore an increased consumption of drugs for these diseases. Objectives: To determine the prevalence of musculoskeletal diseases in general (particularly osteoarthritis) and drugs used for its treatment in a cohort of over 65 years designed in Primary Care Methods: Descriptive cross-sectional study with a stratified random sampling, weighted by age and sex. Information about sociodemographic and health variables was obtained by a semi-structured interview. Participants were invited by mail and then were recruited in the medical office or by telephone. Other variables were obtained from computerized medical records used in Primary Care Results: Sample: 814 individuals ≥65 years. Mean age =77±7.6 years (65-103 years), 51.5% were women. Polypharmacy (≥6 drugs) was present only in the 3.2% of them. Subjective musculoskeletal condition was declared by 66.8% of the subjects, but a musculoskeletal disease diagnosed in medical records was present in 58.1% of them. The prevalence of the different musculoskeletal diseases was: osteoarthritis =49%, rheumatoid arthritis and other rheumatisms =5.5%, gout =4.8%; osteoporosis =17.6%, and other musculoskeletal disease =5.9%. The 4.2% from them had suffered some fracture in the last 10 years, being hip fractures in 1.1%. Medication utilization: 53.8% of the sample did not take any drug to combat these diseases, 29.9% used a single drug chronically, 11.5% 2 drugs and only 4.8% used 3 or more drugs. Medication profile: Analgesics were consumed in 57.9% of them (46.1% paracetamol and other painkillers = 11.8%); nonsteroidalanti-inflammatory drugs (NSAIDs) = 28.1%; corticosteroids =1.7%; drugs for gout = 6.4%, symptomatic slow action drugs in osteoarthritis (SYSADOA) = 6.4% and drugs for osteoporosis (vitamin D, calcium and antiresorptives) = 4.3% Conclusions: The prevalence of musculoskeletal diseases in the elderly of our community is high (especially osteoarthritis) Nearly half of the individuals over 65 years (43.2%) chronically consume any drugs related to musculoskeletal diseases. Among these the most widely used is paracetamol followed by nonsteroidalanti-inflammatory drugs References: Carmona G, Ballina R, Lafflon A. EPISER 2000: prevalence of rheumatic disease in the Spanish population. Rev Esp Reumatol. 2001; 28 (1):18-25. Peña A, Fernández-Lόpez JC. Prevalence and risk factors in osteoartritis. Reumatol Clin 2007; 3 Supl 3: S6-12. De Miguel E, Dominguez A, Morales FJ, Varela C, Riesgo Y. Study of medication in osteoarthritis. Rev Esp Reumatol 2003; 30(1): 12-9. Disclosure of Interest: None Declared